1968
DOI: 10.1113/jphysiol.1968.sp008569
|View full text |Cite
|
Sign up to set email alerts
|

Mammary and whole animal metabolism of glucose and fatty acids in fasting lactating goats

Abstract: SUMMARY1. Measurements were made of milk yield, mammary blood flow and mammary arteriovenous differences during the measurement of substrate entry rate by the isotope dilution method using [U-14C] acids at 094-6-8 mg/min/kg and 6-9 % of total CO2 was derived from each. The udder took up 3-0-5*7 mg/min/kg of tissue and 4-8 % of mammary CO2 was derived from each acid. In the udder 8 and 5-5 % of stearate and oleate were oxidized and 25 % of palmitate. Mammary uptake of stearate was 31-5 % of the total entry rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 22 publications
7
45
0
Order By: Relevance
“…In contrast, in the ruminant animal in the fed state, plasma acetate oxidation contributes 30-60% of the total CO2 output (3,20,21). After a 24-h fast, however, plasma acetate oxidation accounts for 10% or less of the CO2 output (4,22), which is similar to our observations in the overnight fasted human.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, in the ruminant animal in the fed state, plasma acetate oxidation contributes 30-60% of the total CO2 output (3,20,21). After a 24-h fast, however, plasma acetate oxidation accounts for 10% or less of the CO2 output (4,22), which is similar to our observations in the overnight fasted human.…”
Section: Discussionsupporting
confidence: 80%
“…During lactation, glucose is an important intermediate in the metabolism as precursor in lactose synthesis, and an adequate supply is essential for milk secretion (Annison et al, 1968). Borsting and Damgaard (1995) found that lactating mink fed a diet with 12% of ME derived from carbohydrates had to provide about 75% of their glucose requirement by gluconeogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…At higher rates of milk secretion, approaching 2 L/d, the supply of glucose precursors for lactose synthesis can limit lactose synthesis (White & Luick, 1976). In turn, the rate of lactose synthesis exerts a strong control over the level of milk production in ruminants (Annison et al, 1968). us, whenever dietary glucose precursors cannot meet glucose demands the LPR is tapped.…”
Section: Gluconeogenic Demandmentioning
confidence: 99%